Belt and Road Initiative and Southeast Asia's Economic Development: A Case Study of Indonesia - Zarkachi, Imam (Global Focus, 2024)
Belt and Road Initiative (BRI) is China’s economic megaproject and foreign policy grand strategy aiming to bolster the economic growth of developing states throughout regions, including Southeast Asia. Investing massively in infrastructures with the support of the Asia Infrastructure Investment Bank (AIIB) is the key objective of this initiative. This research investigates the advantages of international cooperation under the BRI platform for ASEAN economic development, particularly in Indonesia. This research is analysed using the descriptive qualitative method with journals, books, and reports as the main data resources. The research uses neoliberalism as a theoretical framework to analyse how such international cooperation creates high interdependence amongst states in the international system. The result shows that international cooperation under the BRI economic platform has critically provided aid and assets for developing states to grow their economy in the future. As part of the BRI membership, Indonesia benefits from China’s massive investment in building a high-speed rail link that can boost national economic growth. Keywords: Belt and Road Initiative, Neoliberalism, Economic Development, Southeast Asia, Indonesia